Clinical features and risk factors of acute kidney injury in children with acute paraquat intoxication - Yue Song; Chaofeng Li; Fenglan Luo; Yuhong Tao (Journal of International Medical Research, 2019)
Objective This study aimed to investigate the clinical features and risk factors of acute kidney injury (AKI) in children with acute paraquat intoxication. Methods A retrospective study of 110 hospitalized children with acute paraquat intoxication in West China Second University Hospital, Sichuan University was conducted from January 2010 to May 2017. The Kaplan–Meier method was used to compare the survival rates of children with different AKI stages. Multivariate logistic regression was applied to analyse the risk factors for paraquat-induced AKI. Results AKI occurred in 42 of 110 (38.2%) children. We observed AKI stage 1 in two (4.8%) children, AKI stage 2 in 11 (26.2%), and AKI stage 3 in 29 (69.0%). The survival rate of children in AKI stage 3 (34.5%) was significantly lower than that in children in AKI stage 2 (63.6%) and AKI stage 1 (100%). Multivariate analysis showed that oral ulcers and elevated blood glucose levels were significant independent risk factors for paraquat-induced AKI in children (odds ratio = 4.223 and 5.545, respectively). Conclusions The incidence and mortality rates of paraquat-induced AKI in children are high. Oral ulcers and elevated blood glucose levels are independent risk factors affecting the occurrence of paraquat-induced AKI in children.